Visible-light-mediated sulfonylation of anilines with sulfonyl fluorides - Xin-Qing Li; Qian-Qian Liao; Jun Lai; Yuan-Yue Liao (Frontiers in Chemistry, 2023)
Sulfonylaniline motif plays an important role in pharmaceutical sciences. Developed methods towards this structure are typically lack of good modifiability and stability. In this study, visible-light-mediated sulfonylation of aniline using sulfonyl fluoride as a modifiable and stable sulfonylation reagent is described. A variety of substituted sulfonylanilines were synthesized under mild reaction conditions with moderate to good efficiency. The example of late-stage sulfonylation highlighted the advantage of using sulfonyl fluoride as a sulfonylation reagent. In addition, the crucial influence of counterions on the photocatalyst observed in this system would inspire further research on the photochemistry of sulfonyl fluoride.